2017
DOI: 10.3389/fpls.2017.00012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Genomic Region under Selection in Cultivated Carrot (Daucus carota subsp. sativus) Reveals a Candidate Domestication Gene

Abstract: Carrot is one of the most important vegetables worldwide, owing to its capability to develop fleshy, highly nutritious storage roots. It was domesticated ca. 1,100 years ago in Central Asia. No systematic knowledge about the molecular mechanisms involved in the domestication syndrome in carrot are available, however, the ability to form a storage root is undoubtedly the essential transition from the wild Daucus carota to the cultivated carrot. Here, we expand on the results of a previous study which identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 48 publications
5
26
1
Order By: Relevance
“…QTL for image measurements tended to overlap with QTL for manual measurements, providing confirmation that this pipeline can be used reliably for genetic studies of shoot and root morphology in carrot. Notably, QTL for several traits in this study had various amounts of overlap with previously identified QTL for root swelling on chromosomes 2, 3, 4, and 5 ( Macko-Podgórni et al, 2017 ).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…QTL for image measurements tended to overlap with QTL for manual measurements, providing confirmation that this pipeline can be used reliably for genetic studies of shoot and root morphology in carrot. Notably, QTL for several traits in this study had various amounts of overlap with previously identified QTL for root swelling on chromosomes 2, 3, 4, and 5 ( Macko-Podgórni et al, 2017 ).…”
Section: Discussionsupporting
confidence: 51%
“…Carrot is a globally important crop that originated in Central Asia ( Vavilov , 1992 ; Iorizzo et al, 2013 ) with a secondary center of diversity in Asia Minor ( Banga, 1957 ). A hallmark of carrot domestication is the capacity to develop a thickened storage root ( Macko-Podgórni et al, 2017 ). Selective breeding has since improved taproot size, shape, and uniformity, resulting in forms that have served as the primary delimiter of variety classification since the 1600s ( Simon et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA transcript technology (RNA-seq) is a helpful tool for understanding of differentially expressed genes and the expression patterns of stage-specific genes in plants. RNA-seq has been applied to detect differentially expressed genes under abiotic stresses in diploid rice (Jin et al 2013 ; Fu et al 2017 ). In addition, RNA-seq has also been applied to identify differentially expressed genes in autotetraploid rice compared to diploid rice during pollen development (Wu et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…ABA is a phytohormone involved in the regulation of plant development and plant adaptation to adverse stress conditions [ 78 ]. Several ABC (ATP-binding cassette) transporters were identified to transport ABA using mutant analysis and biochemical characterization [ 79 ].…”
Section: Other Nitrate Transporters In Response To Abiotic Stressmentioning
confidence: 99%